Competition, foreign direct investment and welfare - Mukherjee, Arijit; Sinha, Uday Bhanu (Elsevier, 2016)
In contrast to the usual belief, we show that a lower product-market competition may make the consumers better off and increase welfare when foreign firms strategically choose between export and foreign direct investment (FDI). A lower product-market competition may increase consumer surplus and welfare by inducing FDI. The higher welfare stems from the increased production efficiency under FDI compared to export by the foreign firm.